2015
DOI: 10.1097/hjh.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors related to inappropriately high left ventricular mass in patients with rheumatoid arthritis without overt cardiac disease

Abstract: Two-thirds of patients with RA without overt cardiac disease have iLVM, which is associated with left ventricular systolic dysfunction and concentric geometry. RA per se is a condition closely related to iLVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
(48 reference statements)
2
12
3
1
Order By: Relevance
“…Furthermore, similar to other pathophysiological models (systemic hypertension, diabetes mellitus and aortic stenosis), we showed that the LVSD in patients with RA is closely associated with concentric geometry and increased LV mass (LVM),2 which is inappropriately high in the two-third of them 3…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, similar to other pathophysiological models (systemic hypertension, diabetes mellitus and aortic stenosis), we showed that the LVSD in patients with RA is closely associated with concentric geometry and increased LV mass (LVM),2 which is inappropriately high in the two-third of them 3…”
supporting
confidence: 80%
“…However, in a series of 235 patients with RA we did not find any significant relationship between RA disease activity, inflammatory markers and LVSD,3 though in our patients with active RA the level of disease activity was significantly higher than in the Midtbø's ones (table 1). Similar findings emerged by our analysis performed on 198 patients with RA divided according to the presence/absence of combined circumferential and longitudinal LVSD, defined as the coexistence of impaired scMWS and impaired peak mitral annular systolic velocity S' measured by Tissue Doppler pulsed-wave spectral analysis 4…”
contrasting
confidence: 64%
“…These findings were corroborated by a large echocardiography study of 200 patients,55 as well as preliminary findings from a CMR study assessing treatment-naïve patients with a new diagnosis of RA 56. There are some conflicting reports of higher LV mass in patients with RA in echocardiography studies;57 58 however, this probably reflects the relatively low accuracy of echocardiography-derived LV mass measurement in general (not specific to these studies) and the small sample sizes of the currently available reports.…”
Section: Current Evidence Supporting Non-invasive CV Imaging In Ramentioning
confidence: 69%
“…In patients with RA, a recent cardiac magnetic resonance study showed an increased amount of midwall fibrosis with a non-ischaemic pattern, which again was associated with reduced circumferential strain and higher disease activity 38. In a recent study of 235 patients with RA, reduced scMWS was particularly associated with concentric LV geometry and hypertrophy 14. Lower scMWS is also common in hypertension, in particular when LV concentric geometry is present 11.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported reduced GLS in patients with RA,12 13 and recently, also reduced scMWS was found among patients with RA 14. Further, treatment of 80 patients with RA with an interleukin-1 inhibitor improved GLS, suggesting that RA-associated CV inflammation impairs LV myocardial function 15.…”
Section: Introductionmentioning
confidence: 91%